Community health nursing - Basavanthappa, BT (New Delhi, India : Jaypee Brothers Medical Publishers (P) Ltd., 2003)
May be a comprehesive source book that offers valuable base for designing community healt nursing strategies for the individuals, families, groups and communities.
The concepts of community and health -- Concepts of community health -- Concepts of community health nursing -- Roles and functions of community health nurse -- community health nursing process -- Family health nursing -- Primary health care -- Health education -- Nutrition -- Environmental health -- Maternal and child health -- Immunisation -- Family planning -- Epidemiology -- Communicable diseases -- Non-communicable diseases -- Special health programmes -- Health administration in India -- International health agencies
Includes index.
Keywords: COMMUNITY HEALTH NURSING